An Experimental Study on the Ignition Behavior of Blended Fuels Droplets with Crude Coconut Oil and Liquid Metal Catalyst - Hendry Y. Nanlohy; Helen Riupassa; I Made Rasta; Masaki Yamaguchi (Automotive Experiences, 2020)
This study examines the Ignition characteristics of blended fuel droplets with crude coconut oil and rhodium liquid as a liquid metal catalyst. The ignition behavior was observed by igniting the oil droplet on a junction of a thermocouple, and the droplet evolution recorded with the high-speed camera. The results show that the addition of a liquid metal catalyst successfully reduces the molecular mass of the triglyceride and weakens the bonding force between the carbon chain, and therefore the viscosity and flash point decreases. Moreover, the addition of liquid metal catalysts increased the reactivity of fuel molecules such as C-H, C-C, C = C, and C-O. Changes in the physical properties of the fuel, the geometry of the carbon chain, and molecular mass ease the absorption of heat by the fuel droplet, thereby increasing fuel ignition performances.